Phenomenology of broken habits : philosophical and psychological perspectives on habitual action - Ingerslev, Line Ryberg; Mertens, Karl, 1958- (New York, NY : Routledge, 2024)
"This volume explores the phenomenology of broken habits and their affective, social, and involuntary dimensions. It shows how disruptive experiences impact self-understanding and social embeddedness. The chapters in this volume investigate the epistemic and existential relevance of breakdown of habits and the corresponding kinds of self-understanding available to the agent. The first part focuses on the double-sidedness of habitual life. On the one hand, habits allow us to arrange and navigate in a familiar home world; on the other hand, habits can take hold of us in such a way that we lose our sense of autonomy. The contributors argue that habitual agency is structurally carried by a dynamic that entails both freedom and necessity. As habits enable us to inhabit and thus acquire a world, they also affectively provide a texture and a background for our feeling at home in the world. The chapters in Part 2 focus on the breakdowns of our habitual social and technological life forms and the phenomenology of their affective texture. History and habitual learning are sedimented in our body memory and in our language, and these sedimented layers are partly out of our direct control. Part 3 focuses on the structural openness of habits in relating to one's past and one's traumatic experiences. Part 4 reflects on the ways in which we might become aware of and thus transform or appropriate our culturally given habits. Phenomenology of Broken Habits will appeal to researchers and advanced students working in phenomenology, philosophy of mind, and philosophy of psychology"--
Keywords: Habit breaking; Behavior modification; Habit (Philosophy); PHILOSOPHY / Movements / Phenomenology; PHILOSOPHY / Mind & Body